Evaluación de la Política Nacional de Salud en el Trabajo, en el Distrito 11D04 Celica, Pindal, Puyango – Salud - Quezada Tuquerez, Juan Carlos (2024)
Occupational health in Ecuador, both in public and private institutions, is undervalued, its application is, to a certain extent, forgotten and in many cases partially fulfilled by obligation rather than conviction. The present research evaluates the application of the National Policy of Health at Work in the District 11D04 Celica, Pindal, Puyango - Salud, of the Ministry of Public Health of Ecuador. In this regard, a methodology with a quantitative approach was used, which applied a technique of collecting information such as the survey of officials of the institution, with which it was possible to determine whether public policy is applied; in addition, that most officials are familiar with it and in the same way as if carrying out activities of the National Policy on Health at Work. However, it is necessary to strengthen this application to cover all officials working in the institution and, in this way, provide health and well-being in a comprehensive manner to those working in the institution.